Optimalisasi Pagar Perimeter terhadap Standart Keamanan oleh Petugas Avsec di Daerah Keamanan Terbatas Bandar Udara Internasional Adi Soemarmo Boyolali - Nabila Rifdah Nuraini; Raden Fatchul Hilal (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
A limited security area is an area used for aircraft movement activities, employee or staff movement, and work equipment for flight activities, passenger and baggage movement that will board the aircraft, and vital installations/objects that are directly related to aircraft operations. The purpose of this study was to determine whether the perimeter fence of the limited security area of Adi Soemarmo International Airport was in accordance with applicable provisions and what efforts were made by Airport Security officers to meet the perimeter fence standards in the limited security area of Adi Soemarmo Boyolali International Airport. This study uses a qualitative approach with the types and sources of data, namely primary data and secondary data. This research was conducted at Adi Soemarmo Boyolali International Airport and the time of implementation of this research was carried out from August 1 to January 11 at the Airport Security (AVSEC) unit. The results of this study are that the condition of the perimeter fence of the limited security area of Adi Soemarmo International Airport is not in accordance with applicable regulations. This can disrupt flight activities and threaten flight safety. Efforts made by Airport Security officers for security are patrols in the perimeter fence area and approaches to the community to prevent unlawful acts.